Strengthening the Capability of a micro-scale Bag Producer “Katbag” through Business Planning and Digital Marketing - Nurqamarani, Adisthy Shabrina; Fadilla, Sarah; Thaha, Abdurrahman Rahim; Juliana, Ari; Ulfa, Cherly Kemala; Rachmawati, Dwi; Kuncoro, Setyo; Priyanto, Agus; Santosa, Agus (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
Micro businesses play a crucial role in Indonesia's economy. Their significance in economic recovery is underscored by their substantial contribution to the labor sector. The community engagement partner,